Perbandingan Hasil Dribble Shooting Dan Dribble Jump Shoot Pada Peserta Ekstrakurikuler Bola Basket Di SMAN 3 Mandau - Rizaldi, Muhammad Ramadani; ., Zulrafli (CV. ITTC INDONESIA, 2024)
The aim of this research was to determine the differences in the results of dribble jumpshoot in basketball extracurricular participants at SMAN 3 Mandau. This type of research is comparative desciptive research. The sample for this research was 20 basketball extracurricular participants at SMAN 3 Mandau. The data collection technique was carried out by looking at the practice of basketball extracurricular participants using the dribble shooting and dribble jumpshoot tests. The results of this study showed that the results of dribble jumpshoot were better than dribble shooting with a known t count of 11,859 > 2,262 an a significant probability of 0,00 < 0,05, then the H0 is rejected and Ha is accepted,therefore there is a significant difference between the results of dribble shooting and dribble jumpshoot in basketball extracurricular participants at SMAN 3 Mandau.